Novel tunable and storage light source generated by a soliton pulse in a micro-ring resonator system for new soliton communication bands - Ali, Jalil (S P I E - International Society for Optical Engineering, 2009)
We propose a novel system of broadband source generation using a common soliton pulse (i.e., with center wavelength at 1.55 µm) propagating within a nonlinear micro-ring resonator system. The system consists of a micro-ring resonator system incorporating an add/drop filter, whereby the large-bandwidth signals can be generated, stored, and regenerated within the system. By using the appropriate parameters relating to the practical device such as micro-ring radii, coupling coefficients, and linear and nonlinear refractive index, we found that the obtained multisoliton pulses have shown the potential of application for dense wavelength-division multiplexing (DWDM), whereby the different center wavelengths of the soliton bands can be obtained via the add/ drop filter, which can be used to increase the communication channel capacity in the communication network. The best free spectra range (FSR) and FWHM of the results obtained are 14 nm and 100 pm, respectively, which allows an increase in channel capacity of at least 10 times in only one center wavelength.